Dual-functional 3-acetyl-2,5-dimethylthiophene additive-assisted crystallization control and trap state passivation for high- performance perovskite solar cells - Saykar, Nilesh G.; Iqbal, Muzahir; Pawar, Mahendra; Chavan, Kashinath T.; Mahapatra, Santosh K. (ACS Applied Energy Materials, 2022)
Defect-mediated charge recombination and successive degradation mainly lag the performance of perovskite solar cells (PSCs). Insufficiency or evaporation of organic cations leaves behind the undercoordinated Pb2+ ions, which act as severe charge recombination centers. Herein, theoretical and experimental insights into crystallization control and defect passivation of MAPbI3 perovskite by the dual-functional 3-acetyl-2,5-dimethylthiophene (ADT) molecule are pre-sented. Density functional theory calculations show that both functional groups of ADT possessing different interaction energies could interact with PbI2. The carbonyl group in ADT shows the dominant interaction with Pb2+ forming an intermediate product that might decrease the crystallization rate. Further, the coordinate bonding between ADT and uncoordinated Pb2+ ions in perovskite leads to defect passivation. The 0.6% ADT-modified PSCs possess an average power conversion efficiency (PCE) of 18.22 +/- 0.80% and the highest PCE of 19.03%, whereas the pristine PSCs exhibit an average PCE of 16.23 +/- 1.32% and the highest PCE of 17.47%. Furthermore, the modified PSCs maintain 80% of the initial PCE up to 650 h during storage at ambient conditions (RH = 35 +/- 5%). The present study shows that the simultaneous crystalization control and defect passivation achieved via an ADT additive engineering approach could be an efficient strategy to enhance the PCE and stability of PSCs.
Keywords: 3-acetyl-2; 5-dimethylthiophene; additive engineering; crystallization control; defect passivation; Perovskite solar cells

Lead-free Cs2AgBiCl6 double perovskite: experimental and theoretical insights into the self-trapping for optoelectronic applications - Rahane, Swati N.; Rahane, Ganesh K.; Mandal, Animesh; Jadhav, Yogesh; Godha, Akshat; Rokade, Avinash; Shah, Shruti; Hase, Yogesh; Waghmare, Ashish; Saykar, Nilesh G.; Roy, Anurag; Salgaonkar, Kranti N.; et al. (ACS Physical Chemistry Au, 2024)
Lead-free double perovskites (DPs) will emerge as viable and environmentally safe substitutes for Pb-halide perovskites, demonstrating stability and nontoxicity if their optoelectronic property is greatly improved. Doping has been experimentally validated as a powerful tool for enhancing optoelectronic properties and concurrently reducing the defect state density in DP materials. Fundamental understanding of the optical properties of DPs, particularly the self-trapped exciton (STEs) dynamics, plays a critical role in a range of optoelectronic applications. Our study investigates how Fe doping influences the structural and optical properties of Cs2AgBiCl6 DPs by understanding their STEs dynamics, which is currently lacking in the literature. A combined experimental–computational approach is employed to investigate the optoelectronic properties of pure and doped Cs2AgBiCl6 (Fe–Cs2AgBiCl6) perovskites. Successful incorporation of Fe3+ ions is confirmed by X-ray diffraction and Raman spectroscopy. Moreover, the Fe–Cs2AgBiCl6 DPs exhibit strong absorption from below 400 nm up to 700 nm, indicating sub-band gap state transitions originating from surface defects. Photoluminescence (PL) analysis demonstrates a significant enhancement in the PL intensity, attributed to an increased radiative recombination rate and higher STE density. The radiative kinetics and average lifetime are investigated by the time-resolved PL (TRPL) method; in addition, temperature-dependent PL measurements provide valuable insights into activation energy and exciton–phonon coupling strength. Our findings will not only deepen our understanding of charge carrier dynamics associated with STEs but also pave the way for the design of some promising perovskite materials for use in optoelectronics and photocatalysis.